2004
DOI: 10.1152/ajpheart.00431.2004
|View full text |Cite
|
Sign up to set email alerts
|

Opening of Ca2+-activated K+ channels triggers early and delayed preconditioning against I/R injury independent of NOS in mice

Abstract: Opening of Ca2+-activated K+ (KCa) channels has been shown to confer early cardioprotection. It is unknown whether the opening of these channels also induces delayed cardioprotection. In addition, we determined the involvement of nitric oxide synthases (NOSs), which have been implicated in cardioprotection induced by opening of mitochondrial ATP-sensitive K+ (KATP) channels. Adult male ICR mice were pretreated with the KCa-channel opener NS-1619 either 10 min or 24 h before 30 min of global ischemia and 60 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 50 publications
(63 reference statements)
4
55
3
Order By: Relevance
“…We have previously demonstrated that activation of mitoK ATP channels elicits strong protection against Ca 2ϩ overload and ischemic injury (23,25,26). These conclusions are well supported by several recent studies (9 -11, 26) that document mitoK ATP channel as the end effector in cardioprotection against ischemia during late preconditioning.…”
Section: Discussionsupporting
confidence: 75%
“…We have previously demonstrated that activation of mitoK ATP channels elicits strong protection against Ca 2ϩ overload and ischemic injury (23,25,26). These conclusions are well supported by several recent studies (9 -11, 26) that document mitoK ATP channel as the end effector in cardioprotection against ischemia during late preconditioning.…”
Section: Discussionsupporting
confidence: 75%
“…However, it is known that these agents produce other effects. For example, paxilline has been shown to inhibit sarco/endoplasmic reticulum Ca 2ϩ -ATPase both in vitro and in vivo, albeit at concentrations higher than were achieved in our experiments (47,52). NS-1619 has also been reported to inhibit complex I of the mitochondrial respiratory chain in tumor cells (30), but again, inhibitor concentrations required to achieve this effect were Fig.…”
Section: Discussionmentioning
confidence: 52%
“…However, the results of several recent studies point to the importance of another set of potassium channels, the BK Ca channels, as critical triggers for the development of a protected phenotype in response to preconditioning stimuli (40,47,56). BK Ca channels are expressed on the plasmalemma of cells in a variety of tissues, including endothelial and vascular smooth muscle cells, and are comprised of a poreforming ␣-subunit and an auxiliary ␤-subunit that modulates channel activity and sensitivity to specific agonists (12,44,48,55,64,66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are one of these important convergence points, due to their critical function in cell survival and death; notably, ATP production and apoptosis [10,12,48]. Key mitochondrial proteins, such as several potassium (K + ) channels [49][50][51][52][53] and the mitochondrial permeability transition pore (mPTP) [48,[54][55][56], act as effectors integrating these upstream signals into cardioprotective responses. The mechanisms by which CYP metabolites alter these important effectors are not well defined and require further experimentation.…”
Section: Ischemic Injury and Cardioprotectionmentioning
confidence: 99%